1984
DOI: 10.4315/0362-028x-47.5.372
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Campylobacter jejuni from Fresh and Frozen Meat and Poultry Collected at Slaughter

Abstract: Approximately 800 fresh and frozen meat and poultry samples collected at the point of slaughter were analyzed for Campylobacter jejuni. C. jejuni and C. coli isolates were never discriminated. Isolation levels of C. jejuni from fresh tissues were 5-fold higher (12.1%) than those from frozen tissues (2.3%). The prevalence of C. jejuni in fresh tissues was also higher when results were compared by animal species rather than by individual tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 0 publications
0
19
1
Order By: Relevance
“…and also by Shih (2000), who reported that 100% of chicken livers and gizzards from retail markets were contaminated with Campylobacter. Conversely, in another study conducted by Stern, Green, Thaker, Krout, and Joseph (1984) Campylobacter spp. were isolated in a lower incidence of 30% from the fresh chicken liver samples.…”
Section: Prevalence Of Campylobacter In Chicken Samplesmentioning
confidence: 90%
“…and also by Shih (2000), who reported that 100% of chicken livers and gizzards from retail markets were contaminated with Campylobacter. Conversely, in another study conducted by Stern, Green, Thaker, Krout, and Joseph (1984) Campylobacter spp. were isolated in a lower incidence of 30% from the fresh chicken liver samples.…”
Section: Prevalence Of Campylobacter In Chicken Samplesmentioning
confidence: 90%
“…found on chicken carcasses [11]. Frozen chickens had lower bacteria counts than fresh chickens [25,102]. The highest levels of recovery usually occurred during the warmer months (Jun-Oct) [52,103,122,128], and more C. jejuni (43-86%) than C. coli (11-39%) were recovered [7,52,95,122].…”
Section: Campylobacter In Humansmentioning
confidence: 98%
“…Outbreaks have been associated with raw or inadequately cooked foods of animal origin, especially milk, and including chicken, turkey and hamburger. The incidence of the bacterium has been found to be 5-10% in red meats and up to 30% in poultry (Stern et al, 1984).…”
Section: Pathogens Of Emerging Concernmentioning
confidence: 99%